Analysis of the safety and efficacy of laparoscopic gastrojejunostomy following neoadjuvant chemotherapy for gastric pyloric obstruction - Hu, Bo; Zeng, Yishan (Frontiers in Oncology, 2025)
ObjectiveTo explore the safety and feasibility of laparoscopic gastrojejunostomy combined with neoadjuvant chemotherapy (NACT) in patients with locally advanced gastric cancer and pyloric obstruction.MethodsWe included patients with locally advanced gastric cancer who underwent laparoscopic gastrojejunostomy (LGJ) or endoscopic stenting (ES) between May 2017 and October 2022. The prognostic nutritional index (PNI) was used to evaluate the patient nutritional status. Platelet-to-lymphocyte ratio (PLR) and neutrophil-to-lymphocyte ratios were used to evaluate the inflammatory status of patients. The Kaplan–Meier method was used to analyze survival conditions, and the log-rank test was used to compare survival differences. A multivariate logistic regression analysis was performed to identify the factors related that might affect the prognosis.ResultsDuring the study period, 41 patients received LGJ and 37 patients received endoscopic stenting (ES). Patients in the ES group had higher rates of postoperative complications, particularly bleeding (0 vs. 16.2%, P<0.05). After two cycles NACT, the proportion of PNI≥45 patients in LGJ group was significantly higher than that in ES group (P<0.05). Furthermore, the proportion of patients with PLR<162 in the ES group was significantly higher than that in the LGJ group (P<0.05), and compared to the ES group, patients in the LGJ group were able to tolerate more cycles of NACT (6 vs. 4 cycles). A higher median survival time was observed in the LGJ group, and the multivariate logistic regression analysis confirmed treatment selection as an independent risk factor for overall survival (HR, 6.362; 95% CI:3.285–12.321, P<0.001).ConclusionNACT after LGJ shows potential for reducing tumor stage and improving patient prognosis.